Genetic association of productive traits, carcass measurements and age at first calving in the genetic evaluation of the Nellore breed - F. L. Menezes; S. I. Araújo; R. B. Lobo; L. R. M. Nakabashi; F. Baldi; N. L. Pavan; G. C. I. Seidel; C. V. Araújo (Tropical Animal Health and Production, 2026)
The aim was to evaluate the genetic association between sexual precocity and productive performance in Nellore cattle. Records of standardized body weights at 120 (W120), 210 (W210), 365 (W365), and 450 (W450) days of age, Longissimus Muscle Area (LMA), backfat thickness (BFT), and age at first calving (AFC) were used. The mixed linear model included the fixed effects of contemporary groups (composed of herd, year, and season of birth, as well as the animal’s sex), in addition to the random effects of direct additive genetic, maternal genetic (for W120 and W210), and maternal permanent environment. The variance components were estimated by the restricted maximum likelihood method. The obtained direct heritability estimates were 0.45, 0.49, 0.42, 0.40, 0.33, 0.19, and 0.08 for W120, W210, W365, W450, LMA, BFT, and AFC, respectively. The Spearman correlations of the animals’ breeding values between the weight development estimates were of a high order, and for the traits of backfat thickness and age at first calving, it was 0.27, indicating a relationship at older ages with the onset of the acceleration of adipogenesis. The genetic gain obtained in AFC (0.48 days) with the correlated response related to LMA and BFT was − 0.05 and − 0.19 days, respectively. The genetic correlations obtained between AFC and the weight development traits were positive, however negative with the carcass-associated traits, indicating that the offspring are reproductively precocious, yet lighter and with a greater finish of subcutaneous fat.

Upper respiratory microbiome composition and associations with air pollution and infant respiratory health: a longitudinal study in Guatemala - Rina Das; Andrew Baldi; Sant-Rayn Pasricha; Lisa M. Thompson; Anaité Díaz-Artiga; Laura Maria Grajeda; John P. McCracken; Kelsey Jesser; Lance Waller; Matthew C. Freeman; Thomas Clasen; Sheela S. Sinharoy (International Journal of Hygiene and Environmental Health, 2026)

Reaction norm models for the evaluation of reproductive and productive performance in Nellore cattle - F. L. Menezes; S. I. Araújo; R. B. Lobo; L. R. M. Nakabashi; F. Baldi; N. L. Pavan; G. C.I Seidel; C. V. Araújo (Tropical Animal Health and Production, 2026)
This study evaluated genotype × environment interactions (G×E) in Nellore cattle for growth, reproductive, and carcass traits using reaction norm models. We analyzed the records of body weight and scrotal circumference at 12 and 18 months. (W365, W450, SC365, SC450), as well as loin eye area (LEA) and subcutaneous fat thickness (SFT), from herds across different Brazilian states were analyzed. A hierarchical one-step reaction norm model was applied, including fixed effects of contemporary groups (herd, year and season of birth, and sex), cow age at calving as a covariate, and random effects for additive genetics, permanent environment, and residuals. Bayesian inference with Gibbs sampling was used to estimate posterior distributions.Sires were classified according to environmental sensitivity into four categories: extremely robust, robust, plastic, and extremely plastic. For most traits, over 90% of sires were classified as robust or extremely robust, indicating stability of ranking across environments. Exceptions were observed for SFT and SC365, where lower correlations between extreme environmental gradients suggested G×E effects. Heritability estimates ranged from 0.07 to 0.32 for body weights and reached up to 0.76 for fat thickness, with higher values observed under more favorable environmental conditions. .These findings underscore the utility of reaction norm models for identifying environmentally robust sires under the variability of tropical production systems, thereby supporting more accurate and efficient selection decisions in genetic improvement programs.

Genetic correlations between carcass traits measured by ultrasonography and semen quality traits in Nellore cattle incorporating genomic information - Camila S. Mussi; Gabriel C. Medeiros; Rafael Espigolan; Fernando Baldi; Marcio R. Silva; José D. Guimarães; Elisangela C. Matos; Joanir P. Eler; Tamires Miranda Neto; José Bento S. Ferraz; Luiz F. Brito (Livestock Science, 2025)

Occurrence of pesticide residues in harvested products of various crops from European conventional and organic farming systems - Paula S. Tourinho; Zuzana Hochmanová; Petr Kukučka; Martina Hronová; Marek Šudoma; Shiva Sabzevari; Francisco Alcón; Josefina Contreras; Nelson Abrantes; Isabel Campos; Isabelle Baldi; Mathilde Bureau; et al. (Journal of Hazardous Materials, 2025)

A holo-omics analysis shows how sugar kelp can boost gut health in Atlantic salmon - Jacob A. Rasmussen; Annette Bernhard; Laurène A. Lecaudey; Varsha Kale; Germana Baldi; Lene S. Myrmel; Martin Hansen; Jaelle C. Brealey; Sarah S.T. Mak; Ida B. Nielsen; Lorna Richardson; Lise Madsen; et al. (Aquaculture, 2025)

Exploring novel circulating biomarkers for liver cancer through extracellular vesicle characterization with infrared spectroscopy and plasmonics - R. Di Santo; F. Verdelli; B. Niccolini; S. Varca; A. del Gaudio; F. Di Giacinto; M. De Spirito; M. Pea; E. Giovine; A. Notargiacomo; M. Ortolani; A. Di Gaspare; et al. (Analytica Chimica Acta, 2024)

Native plant gardens support more microbial diversity and higher relative abundance of potentially beneficial taxa compared to adjacent turf grass lawns - Danielle S. Baldi; Christine E. Humphrey; John A. Kyndt; Tyler C. Moore (Urban Ecosystems, 2023)

Estimating genetic parameters of reproductive, carcass, and meat quality traits in Polled Nellore cattle - M. M. S. Mamede; G. J. M. Rosa; E. C. Eifert; F. B. Lopes; F. Baldi; M. F. Costa; R. D. Sainz; A. S. Carmo; A. S. Mascioli; C. U. Magnabosco (Tropical Animal Health and Production, 2023)

Genomic evaluation of commercial herds with different pedigree structures using the single-step genomic BLUP in Nelore cattle - Marisol Londoño-Gil; Daniel Cardona-Cifuentes; Rafael Espigolan; Elisa Peripolli; Raysildo B. Lôbo; Angélica S. C. Pereira; Ignacio Aguilar; Fernando Baldi (Tropical Animal Health and Production, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

A Role for Extracellular Vesicles in SARS-CoV-2 Therapeutics and Prevention - Jatin Machhi; Farah Shahjin; Srijanee Das; Milankumar Patel; Mai Mohamed Abdelmoaty; Jacob D. Cohen; Preet Amol Singh; Ashish Baldi; Neha Bajwa; Raj Kumar; Lalit K. Vora; Tapan A. Patel; et al. (Journal of Neuroimmune Pharmacology, 2021)

Social-Ecological Functional Types: Connecting People and Ecosystems in the Argentine Chaco - M. Vallejos; S. Aguiar; G. Baldi; M. E. Mastrángelo; F. Gallego; M. Pacheco-Romero; D. Alcaraz-Segura; J. M. Paruelo (Ecosystems, 2020)

Genetic association between temperament and sexual precocity indicator traits in Nellore cattle - T. S. Valente; A. C. Sant’Anna; F. Baldi; L. G. Albuquerque; Mateus J. R. Paranhos da Costa (Journal of Applied Genetics, 2015)

Computer image analysis: an additional tool for the identification of processed poultry and mammal protein containing bones - L. Pinotti; T. Fearn; S. Gulalp; A. Campagnoli; M. Ottoboni; A. Baldi; F. Cheli; G. Savoini; V. Dell’Orto (Food Additives & Contaminants: Part A, 2013)

Limb-specific training affects exercise hyperemia but not sympathetic vasoconstriction - Gregory S. Wimer; James C. Baldi (European Journal of Applied Physiology, 2012)

A survey of dioxins (PCDDs and PCDFs) and dioxin-like PCBs in sheep and goat milk from Campania, Italy - M. Esposito; F.P. Serpe; S. Cavallo; R. Pellicanò; P. Gallo; G. Colarusso; R. D’ambrosio; L. Baldi; G. Iovane; L. Serpe (Food Additives & Contaminants Part B-Surveillance, 2010)

Co-culture of arbuscular mycorrhiza-like fungi (Piriformospora indica and Sebacina vermifera) with plant cells of Linum album for enhanced production of podophyllotoxins: a first report - Ashish Baldi; Abhishek Jain; Nishant Gupta; A. K. Srivastava; V. S. Bisaria (Biotechnology Letters, 2008)

Cyclo-oxygenase-2 (COX-2) inhibition reduces apoptosis in acute myocardial infarction - A. Abbate; F. Limana; M. C. Capogrossi; D. Santini; G. G. L. Biondi-Zoccai; S. Scarpa; A. Germani; S. Straino; A. Severino; F. Vasaturo; M. Campioni; G. Liuzzo; et al. (Apoptosis, 2006)

Mechanisms of protection by pantoprazole against NSAID-induced gastric mucosal damage - M. Fornai; G. Natale; R. Colucci; M. Tuccori; G. Carazzina; L. Antonioli; S. Baldi; V. Lubrano; A. Abramo; C. Blandizzi; M. Del Tacca (Naunyn-Schmiedeberg's Archives of Pharmacology, 2005)

Monte Carlo Inversion of DInSAR Data for Dislocation Modeling: Application to the 1997 Umbria-Marche Seismic Sequence (Central Italy) - S. Stramondo; S. Santini; P. Baldi; M. Dragoni; A. Piombo; S. Salvi; G. Spada (Pure and Applied Geophysics, 2004)

Guanacos and sheep: evidence for continuing competition in arid Patagonia - Ricardo Baldi; S. Albon; D. Elston (Oecologia, 2001)

Modeling coseismic displacements resulting from SAR interferometry and GPS measurements during the 1997 Umbria-Marche seismic sequence - S. Salvi; S. Stramondo; M. Cocco; M. Tesauro; I. Hunstad; M. Anzidei; P. Briole; P. Baldi; E. Sansosti; G. Fornaro; R. Lanari; F. Doumaz; et al. (Journal of Seismology, 2000)